Dietary and lifestyle recommendations for urolithiasis prevention: A systematic literature review. Issue 2 (12th September 2018) - Boarin, Mattia; Villa, Giulia; Capuzzi, Claudia; Remon, Denmart; Abbadessa, Francesco; Manara, Duilio Fiorenzo
Abstract : What are the dietary, fluid intake and lifestyle indications for the disease management and recurrences prevention in patients with urolithiasis? Despite the progress in urolithiasis diagnosis and treatment, its incidence has increased in the last decades and a high rate of recurrence is still a real problem. Dietary and lifestyle modifications represent the most effective preventive measures. Recommendations and evidence available in literature are not always accurate and consistent, negatively affecting patients' education. A systematic review was conducted starting from a research in electronic databases; the study selection process was based on PRISMA indications. Methodological quality and risk of bias were assessed. Data were analysed in three phases: (1) critical review of articles; (2) data extraction; (3) evidence synthesis. Thirty‐six studies were included: researchers used prevalently non‐probabilistic sampling methods and data from several studies derived from small samples, mainly from Western countries. Despite these limitations, the below listed themes for urolithiasis prevention arose: (1) the importance of a prevalently vegetarian regime with a reduced intake of meats and fats, decreasing the risk of stones formation from the accumulation of uric acid; (2) water intake greater than two litres per day is proven to prevent recurrences and drinking beverages, such as decaffeinated coffee, tea, beer and wine, also seems to be associated with a decrease in risk; (3) being physically active and having a healthy lifestyle can help to prevent recurrences. Various dietary and lifestyle modifications have a potential to prevent urolithiasis and recurrences. Clinicians should advise patients to reduce animal proteins and fats, increase fruits and vegetables, and increase water intake, as well as having a healthy lifestyle. Further rigorous methodological studies are needed.